Pyroptosis-triggered pathogenesis: New insights on antiphospholipid syndrome - Tan, Yuan; Liu, Qi; Li, Zhongxin; Yang, Shuo; Cui, Liyan (Frontiers in Immunology, 2023)
APS (antiphospholipid syndrome), referred to as Hughes’s syndrome, is a systematic autoimmune disease characterized with thrombosis formation, poor pregnant manifestations, and proinflammatory response. Pyroptosis is a form of lytic programmed cell death, and it aggravates autoimmune diseases progression via activating NOD-like receptors, especially the NLRP3 inflammasome and its downstream inflammatory factors IL (interleukin)-1β and IL-18. However, the underlying mechanisms of pyroptosis-induced APS progression remain to be elucidated. ECs (endothelial cells), monocytes, platelets, trophoblasts, and neutrophils are prominent participants in APS development. Of significance, pyroptosis of APS-related cells leads to the excessive release of proinflammatory and prothrombotic factors, which are the primary contributors to APOs (adverse pregnancy outcomes), thrombosis formation, and autoimmune dysfunction in APS. Given the potential of pyroptosis biomarkers serving as the therapeutic targets of APS, and pyroptosis-associated medicines have been investigated and made encouraging advancements. Therefore, this review would systematically expound the molecular mechanisms of pyroptosis, and elaborate the role of pyroptosis-mediated cellular effects in APS progression. Lastly, the prospective therapeutic approaches for APS would be proposed based on the regulation of pyroptosis.